Utility estimations of different health states of patients with type I, II, and III spinal muscular atrophy in China: A mixed approach study with patient and proxy-reported data - Hu, Jiahao; Zhu, Lin; Bao, Han; Liu, Yuhan; Xing, Huanping; Kang, Qi; Jin, Chunlin (Frontiers in Public Health, 2022)
Introduction: Spinal muscular atrophy (SMA) is a rare autosomal-recessive neuromuscular disease. Utility values (‘utilities’) are used in health economic analyses regarding the desirability of health outcomes such as a certain health state or change in health states over time. There is no utility data of Chinese patients with SMA. Materials and Methods: Vignettes were developed for pediatric neurologists to value the utility of Chinese patients with Type I SMA. A Mixed patient/proxy derived approach using EQ-5D-Y-3L, EQ-5D-3L and CHU9D was adopted to estimate the utility data of different health states of patients with Type II and III SMA. Result: The utility of Type I SMA patients ranged from 0.19 to 0.72 with the health state improved from “permanent ventilation” to “walking”. The utility of children patients with Type II and III SMA derived from EQ-5D-Y-3L ranged from 0.33 to 0.82 while that derived from CHU9D ranged from 0.46 to 0.75. The utility of adult patients with Type II and III SMA measured by EQ-5D-3L ranged from 0.30 to 0.83. Conclusion: The better health states the patients with SMA were in, the higher were the health utilities. The utilities derived from population with different age and disease subtypes were not statistically different when patients with SMA were in the same health states. We recommend further studies on the Chinese specific value set for EQ-5D-Y-3L and other PBMs for children to derive more robust utility data.